PEMILIHAN KEPALA DAERAH MELALUI DPRD DALAM SISTEM KETATANEGARAAN INDONESIA - Micze Ridua, Srye (Fakultas Hukum Universitas Kristen Indonesia, 2025)
The discourse of returning the regional head election system from direct election by the people to election through the DPRD has become a hot debate in Indonesia. This study examines the constitutional legitimacy of the regional head election system through the DPRD within the framework of the Indonesian constitutional system. The 1945 Constitution of the Republic of Indonesia Article 18 paragraph (4) states that regional heads are